Synthesis and Characterization of Conducting Poly-N-isopropylacrylamide-N-vinylcarbazole Polymers - Shashidhar; Ramprasad; Basavaraja, C.; Vishnuvardhan, T.K. (Asian Journal of Chemistry, 2012)
Polymers containing poly-N-isopropylacrylamide (PNI) and N-vinyl carbazole (nvc) were synthesized by dissolving different weight percentages of N-vinyl carbazole (10, 20, 30 and 40 %) during the polymerization of N-isopropylacrylamide. The structure and morphology of the poly-N-isopropylacrylamide-N-vinyl carbazole (PNI-nvc) polymer matrix were identified by UV-visible, fluorescence spectra and atomic force microscope (AFM). Further, the electrical conductivity in the temperature range of 300-525 K showed a semiconducting behaviour with a negative temperature coefficient of resistivity (TCR). In addition, the conductivity data were characterized by three different regions with increasing temperature.